PENGARUH LATIHAN FISIK TERHADAP SISTEM KARDIOVASKULAR - Tyaradhia Ranita Eltidar (Yayasan Pendidikan Medika Indonesia, 2021)
Physical activity is any bodily movement that increases energy expenditure. Physical activity in the form of physical exercise can increase the fitness index of the cardiovascular system. Physical exercise can directly affect the cardiovascular system. The effects can be either acute or chronic. The purpose of this paper is to determine the effect of physical activity on the cardiovascular system. The method used is literature research by searching for keywords physical activity, cardiovascular, and blood exercise on Google Scholar and Pubmed. Searching the literature from both national and international journals then summarizes the discussion topics and compares the results presented in the articles. From several studies conducted, the effect of physical activity on the cardiovascular system is prevention of cardiovascular disease, prevention of diastolic dysfunction, left ventricular adaptation, increased stroke volume, increased cavity volume, thickening of the heart wall, decreased heart rate, improved myocardial perfusion, and changes in lipid profile in the form of increase in HDL.